ANTONIO CHAS AGUIÓN (ed.), «Corte y poesía en tiempos de los primeros Trastámara castellanos: lecturas y relecturas», Berlin, Bern, Bruxelles, New York, Oxford, Warszawa, Wien, Peter Lang, 2022, 290 pp. - García Gutiérrez, Sandra (Lectura y signo, 2022)
Reseña